Nominal and real disturbances and money demand in the Chinese hyperinflation - Ellis W. Tallman; De-piao Tang; Ping Wang (Federal Reserve Bank of Atlanta, 2002)
This paper reexamines the dynamics of hyperinflation by allowing variability in the relative price of capital goods in units of consumption goods that reflects interactions between the real and monetary sectors. The theory generates empirically testable implications that suggest expanding the standard Caganian money demand function to include both anticipated inflation and relative price effects in a nonlinear fashion. Employing data from the post-World War II Chinese hyperinflationary episode, the empirical findings suggest that conventional econometric investigations of money demand during hyperinflation overlook important nonlinear interactions between real and monetary activities and, hence, underestimate the welfare costs of hyperinflation.
Keywords: 330; Inflation (Finance); China; Economic conditions - China